Impact of varying doses and application methods of metribuzin on productivity and profitability of wheat (Triticum aestivum) under different tillage systems - AHLAWAT, ISHA; KAMBOJ, B R; YADAV, DHARAM BIR; DAHIYA, GARIMA; ABHISHEK,; RANA, ANJALI (The Indian Journal of Agricultural Sciences, 2023)
Addressing the imperative of aligning food production with the escalating global population necessitates the identification of sustainable land management strategies. In the Indo-Gangetic Plains of India, weed infestation causes a significant threat to wheat (Triticum aestivum L.) productivity. To address this concern, a field experiment was conducted during the winter (rabi) seasons of 2021–22 and 2022–23 at the research farm of CCS Haryana Agricultural University, Rice Research Station, Kaul, Haryana. The primary objective of this experiment was to assess the effects of varying doses and application methods of metribuzin on the productivity and profitability of wheat crop under zero and conventional tillage systems. Notably, the application of post-emergence (POE) metribuzin at a dose of 350 g/ha as a urea-mix broadcast at 35 days after sowing (DAS) in combination with pinoxaden (PDN) exhibited notablebenefits in terms of productivity and economic viability of wheat. This treatment yielded significantly higher number of effective tillers/mrl (111 in zero tillage; 112 in conventional tillage) and grain yield (5,573 kg/ha in zero tillage; 5,972 kg/ha in conventional tillage). Moreover, the treatment combination of metribuzin at 350 g/ha as a urea-mix broadcast and pinoxaden applied at 35 DAS resulted in the highest net returns and benefit-cost ratio under both tillage systems.